The Status of Middle Schools in the Southeastern United States: Perceptions and Implementation of the Middle School Model - Ryan Alverson; Mike DiCicco; Shawn A. Faulkner; Chris Cook (Middle Grades Review, 2019)
For more than 100 years, education communities have debated how best to educate the young adolescent. Proponents of both the junior high school model and the current middle school model have advocated for a specialized approach to educating adolescents that emphasizes the developmental needs of students. To accomplish this, various organizational structures and instructional approaches are recommended. This survey study examines the perceptions of these middle school practices and the implementation of those practices in middle schools in the Southeastern region of the United States. We note several key trends in our results and highlight key differences in perception of importance and implementation of middle school components and strategies compared to the most recent large scale survey administered by McEwin and Greene (2011).
Keywords: middle school; junior high school; adolescent